Corpus Callosum in ADHD Children and their Siblings - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
The global brain size and a midline area of corpus callosum were measured by MRI in 15 boys with ADHD (mean age 10 years) and compared with 15 healthy male siblings of children with ADHD of the same age.